MANAGEMENT OF WORK TRAINING INSTITUTIONS BASED ON THE NEEDS OF BUSINESS AND INDUSTRY IN IMPROVING THE COMPETENCE OF GRADUATES - Candrawinata, Lalan; Rostini, Deti (Jurnal Konseling Pendidikan Islam, 2025)
This research is motivated by the rapid development of business and industry that demands a flexible and adaptive workforce to changes in technology and operational systems. The purpose of this research is to analyze and develop a management system of Job Training Institutions (LPK) based on industry needs in order to improve the competence and competitiveness of graduates. Using W. Edwards Deming's theory of Total Quality Management (TQM) and the PDCA cycle (Plan-Do-Check-Act), this study applied a qualitative approach. The results showed that training planning was conducted in a participatory manner with industry partners to identify competency needs, but still faced obstacles in adjusting to industry demands. Training implementation has been project-based and applicable, involving industry practitioners and strengthening soft skills, but not yet optimal. Program evaluation has involved external competency testing, although it is still internal and informal. Follow-up in the form of entrepreneurial assistance and alumni monitoring is carried out, but it is not yet systematic and sustainable. The main obstacles include limited facilities, instructor competence, and curriculum adaptation. In conclusion, industry needs-based job training management has a significant effect on improving graduate competencies, with the involvement of industry partners as a key success factor.